Experience with transjugular liver biopsy. Issue 11 (November 1983) - Bull, H J; Gilmore, I T; Bradley, R D; Marigold, J H; Thompson, R P
Abstract : The results of 193 transjugular liver biopsies performed with a modified needle are described. An adequate specimen was obtained in 97%, and complications were rare, although puncture of the liver capsule does occur and caused bleeding in two patients. Fever after the procedure was reduced by ultrasonic cleaning of the needle. Although not easy, this technique is safe and preferable in the management of selected patients, but in most patients percutaneous biopsy is to be preferred.